Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 487345 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Senecio L.", "TaxonKey is Blumea lacera var. commersonii DC., 1836", "TaxonKey is Senecio giorgii De Wild.", "TaxonKey is Blumea lacera var. javanica (Blume) J.Kost.", "TaxonKey is Blumea lacera var. blumei DC.", "TaxonKey is Senecio ambrosioides Mart.", "TaxonKey is Carduus eriocephalus C.Winkl.", "TaxonKey is Antennaria zosonia H.S.Pak", "TaxonKey is Blumea lacera (Burm.fil.) DC.", "TaxonKey is Blumea lacera var. subdivaricata H.Kost., 1972", "TaxonKey is Cotula cotuloides (Steetz) Druce", "TaxonKey is Cirsium Adans., 1763", "TaxonKey is Cotula hispida (DC.) Harv.", "TaxonKey is Cotula L.", "TaxonKey is Senecio leucopappus Bojer ex DC.", "TaxonKey is Cirsium minganense Vict.", "TaxonKey is Mikania F.W.Schmidt, 1795", "TaxonKey is Antennaria nivalis Ten. ex Nyman", "TaxonKey is Lycoseris Cass.", "TaxonKey is Blumea lacera var. microcephala J.Kost., 1941", "TaxonKey is Blumea lacera var. hymenophylla (DC.) C.B.Clarke, 1876", "TaxonKey is Blumea lacera var. depokensis Hochr., 1934", "TaxonKey is Blumea lacera var. meraukensis J.Kost., 1941", "TaxonKey is Blumea lacera var. amboinensis J.Kost., 1941", "TaxonKey is Senecio maderensis DC.", "TaxonKey is Blumea lacera var. glandulosa Hook.fil.", "TaxonKey is Antennaria polyphylla Greene ex C.F.Baker", "TaxonKey is Chaetanthera Nutt.", "TaxonKey is Carduus L.", "TaxonKey is Antennaria nordhagiana Rune & Rønning", "TaxonKey is Antennaria hendersonii Piper", "TaxonKey is Carduus casabonae L.", "TaxonKey is Blumea javanica (Blume) Zoll. & Moritzi" ] }, "HasCoordinate is true" ] } The dataset includes 487345 records from 700 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007507-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences